Pembiasaan Hafalan Do’a Harian untuk Meningkatkan Kemampuan Menghafal Santri TPQ Syubbanul Qur’an, Jambangan, Surabaya (Lembaga Pengembangan Kinerja Dosen, 2026)
This Community Service (PKM) activity aims to improve the memorization skills of students through a program to familiarize them with memorizing daily prayers at the Syubbanul Qur'an Islamic Boarding School (TPQ) in Jambangan, Surabaya. The background to this activity is based on the low ability to memorize daily prayers of students and the lack of habituation in daily life due to limited mentoring in the family environment. The method used in this activity is the Asset Based Community Development (ABCD) approach which emphasizes the utilization of potential and assets owned by the community. The stages of the activity include discovery, dream, design, and destiny which are carried out systematically and participatory. Data collection techniques are carried out through observation and interviews to determine the development of students' memorization skills and the effectiveness of the program. The results of the activity show an increase in the ability to memorize daily prayers, marked by an increase in the number of memorizations, fluency in pronunciation, and increased self-confidence of students. In addition, this program also has an impact on the formation of religious character, discipline, and positive habits in daily life. The program's success was supported by the active involvement of the ustadz/ustadzah (Islamic teacher) and parents, as well as a conducive learning environment. Despite several obstacles, such as differences in student abilities and time constraints, the program remained effective. Thus, the habit of memorizing daily prayers has proven to be an effective strategy for improving memorization skills and sustainably shaping the students' religious character.